Efektivitas Ekstrak Bawang Putih Tunggal Terhadap Gambaran Histopatologi Ginjal Dan Kadar Ureum Kreatinin Rattus Novergicus Yang Mengalami Dislipidemia - Rambe, Natasya Septiana; Suandy, Suandy; Chiuman, Linda (Syntax Literate, 2025)
Heart disease and kidney failure are both increased by dyslipidemia. There are a lot of antioxidant and nephroprotective chemicals in just one clove of garlic (Allium sativum L.), including allicin, flavonoids, and organosulfur compounds. This study set out to examine the effects of a single garlic extract on the urea, creatinine, and uric acid levels in rats with dyslipidemia (Rattus norvegicus). There was an examination of the renal histopathology picture as well. This research used an experimental tack by using a control group design with pre- and post-tests. Each of the four groups consisted of 24 male Wistar rats' tails: the control group (aquades), the experimental group (simvastatin 2.1 mg/kgBB), the garlic extract alone group (200 mg/kgBB), and the highest dose (400 mg/kgBB). Each group followed a high-fat diet for a full month. Both the 200 mg/kgBB and 400 mg/kgBB doses of garlic extract significantly decreased the levels of ureum, creatinine, and uric acid (p<0.05) as compared to the negative control group. Kidney histopathology also revealed improvement, with less congestion, necrosis, and cell death. The positive control and the 400 mg/kgBB group showed similar effects after delivery. Rats with dyslipidemia showed improvements in renal histology and decreased levels of ureum, creatinine, and uric acid after administration of a single garlic extract.